REVOLUSI INDUSTRI 4.0 DAN DISRUPSI, TANTANGAN DAN ANCAMAN BAGI PERGURUAN TINGGI - Bukman Lian (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Challenges in the industrial era 4.0 were identified as 1) improvement of information technology security; 2) increasing the reliability and stability of the production machine; 3) improvement of skills; 4) the reluctance of stakeholders to change; and 5) loss of many jobs due to automation. Disruptive changes overthrow the prevailing system until a fundamental change does not have to be ignored. This means that universities are not free from the threat of being disrupted if they do not immediately make changes and adjust their role in the world of education. These challenges and changes, asked college continue to carry out various roles, such education and teaching, development, and dissemination, as a storehouse of knowledge for the community. The Challenge of Higher Education in Indonesia in the era of the Industry refers to the hope of having world-class universities and can survive and develop according to demands in the era of industrial revolution 4.0.